PENGARUH SISTEM PENGUKURAN KINERJA KOMPREHENSIF DAN PEMBERDAYAAN PSIKOLOGIS TERHADAP KOMITMEN ORGANISASI - Khusnah, Hidayatul; Putra, Riyan Sisiawan (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
A comprehensive performance measurement system is part of the management control function. Overall activities undertaken by employees in strategic planning, budgeting, implementation, and performance evaluation are influenced by the management. This study aims to examine the effect of a comprehensive performance measurement system on psychological empowerment and organizational commitment, as well as the effect of psychological empowerment on organizational commitment at Unusa. Hypothesis testing in this study using Structural Equation Modeling - Partial Least Square (SEM-PLS) with WarpPLS 3.0 software. The results of this study indicate that a comprehensive performance measurement system positively affects the psychological empowerment and organizational commitment. The latest findings of psychological empowerment have a positive effect on organizational commitment.